Microglial and neurogenic alterations in hypothalamus due to acute stress - Infantes-López, M. Inmaculada; Nieto-Quero, Andrea; Zambrana-Infantes, Emma; Chaves-Peña, Patricia; Tabbai-Amal, Sara; Pedraza-Benítez, María del Carmen; Pérez-Martín, Margarita (My University, 2021)
Microglial cells are an important glial population known to be involved in several biological processes such as stress response. These cells engage an activated state following a stress insult that may lead to nervous tissue damage, including new cell generation impairment. This has been widely studied in regions with notable neurogenesis such as de hippocampus, however, the effect in other regions with fewer yet relevant neurogenesis remains partially unknown. One of them is the hypothalamus, a key vegetative control center playing an important role in stress response. Moreover, most of the stress models studied concern neuroinflammatory and neurogenic changes due to a chronic stressor but not a single stress event. Given the repercussion of these processes alone, it would be interesting to elucidate the relationship between microglial response, hypothalamic neurogenesis, and acute stress. This project focuses on studying acute stressed C57BL/6J mice, both at the histological and molecular level. An intense stressor combining water immersion and movement restriction was performed. Using immunohistochemical and molecular analysis with Luminex, we could analyze microglial distribution and morphology, neurogenesis, and inflammatory environment in the hypothalamic parenchyma (paraventromedial, ventromedial and arcuate nucleus).
This study was supported by FEDER/Ministerio de Ciencia, Innovación y Universidades – Agencia Estatal de Investigación from Spain (PSI2017-83408-P to Pedraza C.), and Ministerio de Educación, Cultura y Deporte from Spain (FPU16/05308 to Nieto-Quero A).
Keywords: Neuroinflamación; Stress; Microglia; Neuroinflammation